Performing Gender And Rural Tourism: An Analysis Of Homestay’s Operators In Penang Island - Hayrol Aziz, Farah Syazwani; Selamat, Nor Hafizah (2016)
In the field of tourism, the issues of authenticity and post-modern experience has been advanced to the point where such experiences can be seen as authentic and meaningful to tourists even within the context of a largely commoditised and ‘staged’ experiential setting. The study of generic ‘performed events’ has been much debated within tourism from a variety of perspectives including: semiotics of tourism; marketing; sociology and anthropology. However, the study on the issue of performing gender stereotypical roles at a commoditized locations such as in the homestay programme is still limited. This study will look at how male and female operators in the homestay programme performed and negotiated their roles within the framed events of receiving tourists at their home. Using a qualitative approach, this study examines how homestay operators performing dual performances between the performance of “staged experiences” and performance of “everyday lives”. Theorizing about negotiation of performance is vital in the study of gender and tourism as it offers a perspective on value and meaning on the roles’ performed by these male and female operators. It is argued here that ‘tourist experience’ is a production of “staged” performance in order to create an ‘authentic’ experience.